CloudThinking as an intelligent infrastructure for mobile robotics - Aguiar, Rui L.
Mobile robotics is a transforming field that presents a varying set of challenges. The discussion on the autonomy of (self-powered) robots is not settled, and as the communication infrastructure evolves, centralized concepts become more attractive over distributed concepts. This paper presents the CloudThinking architecture applied to intelligent cloud-based robotic operation. CloudThinking offloads most of complex robotic tasks to a central cloud, which retrieves inputs from the environment as a whole in order to instruct the robots to perform its actions. CloudThinking is a natural approach to the orchestration of multiple specialized robotic systems, defining the best mechanisms for reaching a goal. Furthermore, this architecture provides a set of automatic features which can be useful for application developers. These features can fully exploit novel cloud tools development as it becomes available, providing a time-resilient infrastructure of easy upgrade. The resulting approach has the potential to create a different set of market for robotic application developers.